Value Chain Model for Value Addition of Local Ingredients to Gastronomy Tourism’s Activities in Phuket Province - Maneerat, Prutthiyaporn; Jaroenwisan, Kaedsiri (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
A value chain is a business strategy that entrepreneurs or manufacturers can use to create value as an ingredient in the process of production. This academic article focused on the value chain model for the value addition of local ingredients to gastronomic tourism activities in Phuket. The value chain model drives the process of production through to the delivery process. The purpose was to add value to productivity, in the process, creating value, a competitive advantage and experiences for tourists. The value chain model for creating value from local raw materials for gastronomy tourism activities in Phuket consists of three processes: 1) Upstream management, which includes farm systems, product stories, creative industries, and sustainable tourism; 2) Middle Stream management, which includes logistics management, sales, and marketing; and 3) Downstream management, which includes, among other things, gastronomy tourism activities such as cooking classes, food festivals, and local food products.